Immune-modulatory genomic properties differentiate gut microbiota of infants with and without eczema - Oh, Seungdae; Yap, Gaik Chin; Hong, Pei-Ying; Huang, Chiung-Hui; Aw, Marion M.; Shek, Lynette Pei-Chi; Liu, Wen-Tso; Lee, Bee Wah (PloS one, 2017)
Gut microbiota play an important role in human immunological processes, potentially affecting allergic diseases such as eczema. The diversity and structure of gut microbiota in infants with eczema have been previously documented. This study aims to evaluate by comparative metagenomics differences in genetic content in gut microbiota of infants with eczema and their matched controls. Stools were collected at the age of one month old from twelve infants from an at risk birth cohort in a case control manner. Clinical follow up for atopic outcomes were carried out at the age of 12 and 24 months. Microbial genomic DNA were extracted from stool samples and used for shotgun sequencing. Comparative metagenomic analysis showed that immune-regulatory TCAAGCTTGA motifs were significantly enriched in the six healthy controls (C) communities compared to the six eczema subjects (E), with many encoded by Bifidobacterium (38% of the total motifs in the C communities). Draft genomes of five Bifidobacterium species populations (B. longum, B. bifidum, B. breve, B. dentium, and B. pseudocatenulatum) were recovered from metagenomic datasets. The B. longum BFN-121-2 genome encoded more TCAAGCTTGA motifs (4.2 copies per one million genome sequence) than other Bifidobacterium genomes. Additionally, the communities in the stool of controls (C) were also significantly enriched in functions associated with tetrapyrrole biosynthesis compared to those of eczema (E). Our results show distinct immune-modulatory genomic properties of gut microbiota in infants associated with eczema and provide new insights into potential role of gut microbiota in affecting human immune homeostasis.